Evaluation of The Distance Learning System Success of Apparatus Training: User Satisfaction Mediation - Azwar Azwar; Siti Aisyah; Adji Suradji Muhammad (Program Studi S3 Ilmu Manajemen, 2021)
This research aims to find out the influence of system quality and service quality of distance learning system on user satisfaction and the achievement of learning outcomes of trainees during the covid-19 pandemic era at the Financial Education and Training Agency of Makassar. In addition, the study also aims to examine how the role of user satisfaction in mediating the influence of system quality and service quality of distance learning systems on learning outcomes. This study used data obtained from respondents through questionnaires and quantitative approaches through component or variant-based of Structural Equation Modelling (SEM) techniques with Partial Least Square (PLS). The results show that in general the distance learning system has fully run well and successfully based on indicators of DeLone and McLean model. The system quality significantly has positive influence on user satisfaction, service quality significantly has positive influence on user satisfaction and user satisfaction also significantly has positive influence the learning outcomes. Meanwhile, user satisfaction can be a mediator in strengthening the influence of system quality service quality on learning outcomes. Financial Education and Training Agency of Makassar is expected to maintain and improve the quality of systems and services in the existing distance learning system in order to maintain and improve the satisfaction of trainees and learning outcomes.